Strain differentiation of Newcastle disease viruses by laboratory tests - MISHRA, S; KATARIA, J M; VERMA, K C; MISHRA, J P (The Indian Journal of Animal Sciences, 2013)
Studies on characterization and strain differentiation of 3 Newcastle disease virus isolates originated from the chicken, guinea fowl and pigeon were undertaken by pathogenicity tests and by some unrelated laboratory tests. Chicken and guinea fowl isolates were viscerotropic velogenic in nature, whereas pigeon isolate was mesogenic in nature. All the 3 isolates have similar Lype of haem agglutinating properties indicating the presence of same terminal carbohydrate residues. Among the 3 isolates, pigeon isolate was inactivated very soon at 56Â°C, whereas guinea fowl isolate resisted heat for longer time. As far as elution pattern is concerned, chicken isolate was a rapid eluter while guinea fowl and pigeon Isolates were slow eluters. However, rate of elution was very slow for pigeon isolate than guinea fowl isolate. No relationship could be established between the pathogenicity indices and other laboratory tests.